Labiopalatognathoschisis: A Systematic Review of Risk Factors, Diagnosis, and Therapeutic Approaches: A Systematic Review of Risk Factors, Diagnosis, and Therapeutic Approaches - Suryadharma, Kadek A.; Rahma, Baiq Suyatmin; Candra, Tania Happy; Maya, Elyana Labib; Airlangga, Arya P.; Ningsih, Nur A. Ahya; Arigi, Lalu Ahmad Gamal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Labiopalatognatoschisis, or cleft lip with or without cleft palate, is one of the most common craniofacial congenital anomalies, associated with functional, aesthetic, and psychosocial challenges. Its management is complex, requiring early detection and multidisciplinary care. This study aimed to identify major risk factors, evaluate diagnostic approaches, and review effective management strategies. A systematic literature review was conducted using PubMed, Google Scholar, and ProQuest for articles published between 2013 and 2023 with the terms “labiopalatognatoschisis,” “cleft lip,” and “cleft palate.” Studies addressing etiology, diagnosis, or management were included, while irrelevant publications were excluded. Findings showed that genetic predisposition, family history, maternal nutritional deficiencies, teratogenic drug use, and prenatal exposure to harmful substances are key risk factors. Prenatal ultrasonography and MRI can aid diagnosis, though cleft palate detection remains limited. Management requires staged surgical repair and coordinated input from plastic surgeons, ENT specialists, orthodontists, pediatricians, and speech therapists. The review concludes that enhancing prenatal screening, integrating psychosocial support, and advancing research on diagnostic accuracy and long-term multidisciplinary outcomes are crucial for improving prognosis and quality of life.